Upaya Pencegahan Kejadian Hipertensi Melalui Edukasi Lansia di Kelurahan Sawah Padang Aua Kuning, Payakumbuh Selatan, Sumatera Barat: Efforts to Prevent Hypertension Incidents in the Elderly Through Education in Sawah Padang Aua Kuning Village, South Payakumbuh, West Sumatra - Rita, Rauza Sukma; Sulthani, Muhammad Zhorif; Annisa, Nadia Rizki; Fajri, Rahmi Eka; Alhamda, Nadhiyatul; Rizaldi, Fajri; Santika, Annisa Yulia (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
The elderly are the age group over 60 years. The elderly are at risk of various disease burdens such as diabetes mellitus, Alzheimer's, hypertension, and others. Hypertension is a condition characterized by an increase in blood pressure above 140/90 mmHg. Elderly people are at risk of developing hypertension due to the influence of age and the process of atherosclerosis. Many efforts can be made to prevent hypertension, namely maintaining a healthy diet, physical activity, and reducing stress. This effort can be carried out well if it is supported by ongoing education for the elderly regarding hypertension. This activity aims to provide education to the elderly to prevent hypertension and hopefully reduce the incidence of hypertension in the elderly. The method of this activity is carried out by providing education about hypertension and the efforts that need to be made to prevent hypertension to the elderly who attend Posyandu activities at the Sawah Padang Aua Kuning Subdistrict Health Center. The media used was hypertension education posters. After the counseling activity, a question and answer session was held regarding hypertension material. Many of the elderly asked questions and were enthusiastic about the material presented. It is hoped that in the future hypertension education can be carried out regularly to increase the knowledge of the elderly.